Intensification of Rainfed and Irrigated Vegetable Production Systems - World Vegetable Center (International Food Policy Research Institute, 2017)
This research was undertaken aiming to improve farm fied productivity and profitability in Mali. In this research, demonstration trials were implemented by farmer's communities in collaboration with the local non-government organization L?Association Malienne d?Eveil au D?veloppement Durable (AMEDD). Vegetable biodata were collected for Bougouni and Koutiala of Mali and Northern, Uppereast and Upperwest regions of Ghana. Project title: Research Program on Soil & Water Management. Project abstract: As part of the Feed the Future Initiative, the United States Agency for International Development (USAID) is supporting an innovative multi-stakeholder agricultural research program, the Africa Research in Sustainable Intensification for the Next Generation (Africa RISING). The program?s main objective is to identify and validate scalable options for the sustainable intensification of key African cereal-based farming systems to increase food production and improve the livelihoods of smallholder farmers and at the same time conserve or improve the natural resource base. Project website: http://africa-rising.net